A prospective randomized trial comparing dephereline and busereline for ovulation induction in heat-stressed lactating dairy cows - Fernando LÓPEZ-GATIUS (The Journal of Reproduction and Development, 2025)
Climate change is causing heat stress (HS) in dairy cattle. This study aimed to compare the clinical efficacy of two GnRH synthetic analogs, dephereline and busereline, as ovulation inducers under HS conditions. The study population comprised 1,000 lactating dairy cows showing signs of spontaneous estrus which were assigned to the groups: DEPH (489 cows receiving 100 µg of dephereline) and BUS (511 cows receiving 10 µg of busereline) at the time of insemination. Cows were included only once in the study. Treatment with busereline increased the risk of multiple ovulations and twin pregnancies, with an odds ratio (OR) of 1.6, and twin pregnancies, with an OR of 2.8, when compared with dephereline. The likelihood of pregnancy in multiple-ovulating cows was significantly higher in the DEPH group than the BUS group. Collectively, our results comparing two ovulation inducers showed that dephereline treatment may improve the fertility of lactating dairy cows under HS conditions.